Sensitivity Analysis of Vector-host Dynamic Dengue Epidemic Model - Hasan, Md. Rifat; Hobiny, Aatef; Alshehri, Ahmed (Communications in Mathematics and Applications, 2023)
A global health hazard, dengue fever causes or contributes to the deaths of 10,000 people and 100 million cases of symptomatic cases every year in more than half of the globe. The goal of this work is to construct a compartmental vector-borne dengue model that takes into account the typical incidence connection between infected humans and susceptible vectors in order to examine the impact of model parameters that are within our control on the basic reproduction number. In order to determine the basic reproduction number \(R_0\), the next-generation matrix is used. The theoretical study reveals that disease-free equilibrium occurs as a locally asymptotically stable if \(R_0
Keywords: Basic reproduction number (R0); Dengue fever; Metzler matrix; Numerical simulation; Sensitivity analysis; Stability